Psychological Skills of Indonesian Basketball Athletes in Asian Games 18 - Nanda, Fitri Agung; Dimyati, Dimyati (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2019)
Psychological skills in sports science are not new research. This subject has been widely carried out but there are still many limitations particularly on aspects motivation, self-confidence, anxiety control, mental preparation, the importance of the team, and concentration, especially in Indonesian basketball athletes competing in the Asian Games 18. The aims to know skills a comprehensive psychological Indonesian basketball athlete who will compete in the Asian Games 18. Research used a retrospective causal-comparative design or ex post facto. This study was 24 Indonesian national basketball team athletes. The research used The Psychological Skills Inventory for Sports (PSIS-R-5), which was adopted from Mahoney. Analysis of this study used quantitative descriptive with SPSS version 22 software. The results reveal the psychological skills of Indonesian basketball players get the total number of aspects with a mean score of 139.75 the categorized as high. On the results of the study, there is one aspect that gets a score smaller than the other five aspects. That aspect is mental preparation because it requires more psychological training and development skills for Indonesian basketball athletes, especially in aspects of mental preparation to support Indonesian achievements.